Sustainable Innovations in Recycled Textiles (Textile Science and Clothing Technology,, 2018)
This book highlights the environmental and economic benefits of recycling in textiles and fashion; vis-a-vis virgin textiles. Recycling plays an inevitable part when it comes to sustainable innovations in textiles and fashion sector. As basic information pertaining to the benefits, challenges of recycling in textiles are discussed to the sufficient extent in the literature, this book deals with the innovative at the same time, sustainable products made from the recycled textiles.